Mono- and di-thiocarbamate inhibition studies of the δ-carbonic anhydrase TweCAδ from the marine diatom Thalassiosira weissflogii - Silvia Bua; Murat Bozdag; Sonia Del Prete; Fabrizio Carta; William A. Donald; Clemente Capasso; Claudiu T. Supuran (Taylor & Francis Group, 2018)
The inhibition of the δ-class carbonic anhydrase (CAs, EC 4.2.1.1) from the diatom Thalassiosira weissflogii, TweCAδ, was investigated using a panel of 36 mono- and di-thiocarbamates chemotypes that have recently been shown to inhibit mammalian and pathogenic CAs belonging to the α- and β-classes. TweCAδ was not significantly inhibited by most of such compounds (KI values above 20 µM). However, some aliphatic, heterocyclic, and aromatic mono and di-thiocarbamates inhibited TweCAδ in the low micromolar range. For some compounds incorporating the piperazine ring, TweCAδ was effectively inhibited (KIs from 129 to 791 nM). The most effective inhibitors identified in this study were 3,4-dimethoxyphenyl-ethyl-mono-thiocarbamate (KI of 67.7 nM) and the R-enantiomer of the nipecotic acid di-thiocarbamate (KI of 93.6 nM). Given that the activity and inhibition of this class of enzyme have received limited attention until now, this study provides new molecular probes and information for investigating the role of δ-CAs in the carbon fixation processes in diatoms, which are responsible for significant amounts of CO2 taken from the atmosphere by these marine organisms.